Ang. en præsteanssættelse i Bleking år 1660 : Et biskoppeligt brev til belysning af forholdene i Skåne efter afståelsen til Sverige. - Engelhardt, Paul Erik (Kirkehistoriske Samlinger, 1990)
In 1657 the Danish King, Frederik III, declared war on Sweden. It proved disastrous to Denmark, as the hard winter enabled the Swedish King Karl X Gustav, to walk over the ice of the Great Belt in January 1658, thus threatening Copenhagen. This got the panic-stricken Danes to make peace on 26th February 1658 resulting in all counties east of the Sound being ceded to Sweden. The Scanian Bishop, Peder Vinstrup, who had held the bishop’s chair since 1638, accepted the peace terms. In 1658-1659 he assisted the new rulers, and it came to a mutual understanding between him and Karl X; the Bishop became useful to the Swedish King, being able to exercise authority over school and church and consequently over the Scanian opposition too. In August 1658, when Karl X resumed the war against Denmark, Vinstrup might have thought this to be the end of the independence of the Kingdom of Denmark, and he asked God to bless the warfare of the Swedish King. In May 1659 he suggested a deportation of Scanians from the coast along the Sound up into Sweden and to replace them with Swedes, and in August the same yeae he saluted the Swedish army for having captured Nakskov. This exaggerated persistence of supporting the Swedish struggle against Denmark has often been characterized as treason, but Vinstrup’s conduct must be seen in the perspection of his conception of God’s punishment of Denmark, using Sweden as a chastiser, of his admiration of Karl X Gustav, and of the fact that the Peace Treaty of Roskilde allowed the Swedish King to dispose of him, if he resisted the Swedification of Scania. Vinstrup, however slowly changed his attitude, because Sweden didn’t succeed in crushing the Danish Kingdom; this was due to the fact that in February 1659 the Swedes were defeated outside Copenhagen, again in November 1659 at Nyborg, and again in February 1660 in Norway. Karl X’s death in February 1660 further motivated Vinstrup to resist the Swedification of his diocese and insist upon an unchanged Danish church as promised in the peace treaty. So he warns the Swedish Governor General in Malmoe that it is against the Danish law in force that the peasants issue a deed of institution (i.e. an employment letter for a parson or a student applying for a post) without the bishop’s knowledge. This letter is an example of Peder Vinstrup’s growing change af attitude. Also the letter indirectly reflects the hostility that the common people in Scania felt against the Swedish Rule.